Worldview and Behavioural Study of Sports From The Ismalic Perspective Among Sports Offocials in Malaysia - Berhanundin, Abdullah; Badlihisham, Mohd Nasir; Yusaini, Yusof (2016)
A person’s worldview provides a structure to his thoughts and actions. Personal experiences, different kinds of cultural influences, the environment and personal reflections shape a person’s worldview and affects how he perceives and interprets the world around him and thus influences his behavioural pattern. This study was conducted to explore the understanding of officials at the Ministry of Youth and Sports in Malaysia regarding sports from an Islamic worldview and its influence on their behaviour. An instrument, modified from past researches and verified by a panel of experts which attained a considerable level of alpha Cronbach value, was used to measure understanding and behaviour of 349 sport officials obtained through simple random sampling method. The instrument encompassed the domains of faith (aqidah), worship (ibadah) and morality (akhlak) with regard to rulings, regulations and goals in sports from an Islamic worldview. Data were analysed through correlation, Ttest, ANOVA and Simple Regression statistical analysis. Results obtained indicated a high level of understanding of sports from an Islamic worldview. There were significant difference in understanding Islamic worldview based on level of education and grade obtained in the subject of Religious Education. Furthermore, these two variables showed a high positive correlation between the domains of worldview and behaviour among the respondents. However, there was no significant relationship between understanding and behaviour based on type of school stream and length of service. This study implies that an understanding of sports from an Islamic worldview has an influence on the willingness of officials in the Ministry of Youth and Sports in Malaysia to implement shariah compliant sports.